Raiva: origem, importância e aspectos históricos - Babboni, Selene Daniela [UNESP] (2011)
Rabies was described at least 4 millennia ago and is one of the oldest zoonosis. All mammals have cells which are responsible for viral replication, and they are the only ones susceptible to the virus and capable of transmitting it. Due to its lethal evolution, high number of human cases, as well as individuals yearly submitted to post-exposure rabies treatment, rabies remains a worldwide public health problem. The lack of adequate information systems and epidemiological surveillance in most countries does not allow us to know the true magnitude of the problem. The historical period of rabies is extended, because since Aristóteles, it was already considered a contagious disease and because of the bite of dogs, it was feared and known as a lethal disease. Louis Pasteur has provided a major breakthrough, which reached its climax with the first vaccination of a human being in 1885, as well as the creation of the Pasteur Institute in Paris in 1888. The chronology of reabies natural history in this review demonstrates the development in discoveries about the disease since its origin.